Impact of Interest Groups in United Kingdom, as State Member of European Union - Q. Limani, Adnan (European Journal of Sustainable Development, 2016)
Abstract Within the research of the impact of groups of the interest in decision making and policy drafting in member states of European Union was researched in specific manner the United Kingdom one of the main countries, with the most influence in the politics of the European Union, group-interest complex, impact and their acting in the country as well as at the European Union as a state member. In the study we presented also the political system of the United Kingdom with its specifics in which the groups of interest through potential channels influence on its policy drafting analysing and comparing the relation, importance and features that exist between different types and the impact of these groups in political decision making implying interaction with a major number of institutional and political actors. Where it has been possible in particular we are defined for political groups but also on the economical ones through which it influences the drafting of politics and which try to influence the decision making process at all stages, in the manner that different issues that have to do with their interests to enter in agenda as priorities of internal and external politics and to become part of the governing programme of this country. In continuation was explained the reason of selecting United Kingdom as member of European Union and its analysing stands in historical facts and at the importance that this country had on the past and that also today has in the united Europe and that is considered the promoter of processes and developments in the United Kingdom. Keywords: United Kingdom, political system, groups of interest, influencing, European Union